The protective effect of GLP-1 analogue in arterial calcification through attenuating osteoblastic differentiation of human VSMCs. (15th June 2015) - Zhan, Jun-Kun; Wang, Yan-Jiao; Wang, Yi; Tang, Zhi-Yong; Tan, Pan; Huang, Wu; Liu, You-Shuo
Abstract: Background: Arterial calcification is a common event in cardiovascular pathogenesis. Osteoblastic differentiation of vascular smooth muscle cells (VSMCs) is the most important cytopathologic foundation of arterial calcification. Glucagon-like peptide-1 (GLP-1) exerts multiple cardioprotective actions beyond insulinotropic effects through GLP-1 receptor (GLP-1R). However, whether GLP-1 regulates osteoblastic differentiation of VSMCs and associated molecular mechanisms has not been clarified. Methods: The human VSMC differentiation model was established by beta-glycerophosphate (β-GP) induction. The mineralization was measured by Alizarin Red S staining. Protein expression and phosphorylation were detected by Western blot or immunofluorescence. GLP-1R gene expression was silenced by siRNA. Results: The GLP-1 analogue liraglutide dose- and time-dependently inhibited the protein expression of osteoblastic differentiation markers alkaline phosphatase (ALP), osteocalcin (OC), and Runt-related transcription factor 2 (Runx2), phosphorylation of PI3K, Akt, mTOR, and S6K1. Silencing of GLP-1R gene expression by siRNA significantly blocked the effects of liraglutide in ALP protein expression and PI3K/Akt phosphorylation. Conclusion: GLP-1 analogue liraglutide attenuates the osteoblastic differentiation and calcification of human VSMCs through its receptor and subsequent activation of PI3K/Akt/mTOR/S6K1 signaling. GLP-1 analogues may be potential agents for the treatment of cardiovascular diseases. Highlights: GLP-1 analogue liraglutide inhibits the osteoblastic differentiation and calcification of human VSMCs. PI3K/Akt/mTOR/S6K1 signaling is involved in the role of GLP-1 analogue liraglutide. GLP-1 analogues are potential for the treatment of cardiovascular diseases.